Digital Governance Impact on Financial Reporting Timeliness: Company Characteristics Unveiled: Dinamika Ketepatan Waktu Pelaporan Keuangan di Internet: Eksplorasi Karakteristik Perusahaan dan Tata Kelola Dewan - Reny Rahmawati; Slamet Harjatno (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to investigate the factors that influence the timeliness of financial reporting on the internet. By examining a diverse sample of companies, we explore the impact of various company characteristics on reporting timeliness, with a focus on Return On Investment (ROI) and Debt To Equity Ratio (DER). Additionally, we examine the role of the board of directors and the board of commissioners in shaping reporting timeliness. Our findings reveal that company characteristics have a significant effect on reporting timeliness, with the exception of ROI and DER. Furthermore, the board of directors is found to exert a substantial influence on reporting timeliness, whereas the board of commissioners does not exhibit a significant impact. These results shed light on the critical factors influencing financial reporting practices in the digital age and hold implications for regulators, investors, and practitioners seeking to enhance the efficiency and transparency of financial reporting processes on the internet. Highlights: Company characteristics influence reporting timeliness: The study examines how specific company characteristics impact the timeliness of financial reporting on the internet, providing insights into the factors that affect the efficiency of reporting processes. Board of directors' significance: The research highlights the significant role of the board of directors in influencing reporting timeliness, underscoring the importance of effective governance structures and decision-making processes within organizations. Limited impact of board of commissioners: The study reveals that the board of commissioners does not have a significant impact on reporting timeliness, emphasizing the need for further exploration of their role and responsibilities in financial reporting oversight Keywords: financial reporting, timeliness, internet, company characteristics, board governance